Prognostic Effects of Inappropriate Empirical Antimicrobial Therapy in Adults With Community-Onset Bacteremia: Age Matters - Hung, Yuan-Pin; Chen, Po-Lin; Ho, Ching-Yu; Hsieh, Chih-Chia; Lee, Chung-Hsun; Lee, Ching-Chi; Ko, Wen-Chien (Frontiers in Medicine, 2022)
Background: Studies have reported the effects of delayed administration of appropriate antimicrobial therapy (AAT) on the short-term prognosis of patients with bloodstream infections; however, whether there is an age-related difference in these effects remains debated. Methods: In this 4-year multicenter case-control study, patients with community-onset bacteremia were retrospectively categorized into the “middle-aged” (45–64 years), “old” (65–74 years), and “very old” (≥75 years) groups. Two methods were adopted to investigate the prognostic effects of delayed AAT in each age group. First, its effects were respectively investigated, after adjustment for the independent predictors of 30-day mortality. Second, patients in each age group were matched by the closest propensity-score (PS), which was calculated by independent predictors of mortality; the survival curves and Pearson chi-square tests were adopted to disclose its effects in each PS-matching group. Results: Each hour of delayed AAT resulted in an average increase in the 30-day crude mortality rate of 0.2% (P = 0.03), 0.4% (P < 0.001), and 0.7% (P < 0.001) in middle-aged (968 patients), old (683), and very old (1,265) patients, after respectively adjusting the independent predictors of mortality in each group. After appropriate PS-matching, no significant proportion differences in patient demographics, bacteremia characteristics, severity of bacteremia and comorbidities, and 15-day or 30-day crude mortality rates were observed between three matched groups (582 patients in each group). However, significant differences in survival curves between patients with delayed AAT >24 or >48 hours and those without delayed administration were demonstrated in each age group. Furthermore, the odds ratios of 30-day mortality for delayed AAT >24 or >48 hours were 1.73 (P=0.04) or 1.82 (P=0.04), 1.84 (P=0.03) or 1.95 (P=0.02), and 1.87 (P=0.02) or 2.34 (P=0.003) in the middle-aged, old, and very old groups, respectively. Notably, the greatest prognostic impact of delayed AAT >24 or >48 hours in the very old group and the smallest impact in the middle-aged group were exhibited. Conclusion: For adults (aged ≥ 45 years) with community-onset bacteremia, the delayed AAT significantly impacts their short-term survival in varied age groups and the age-related differences in its prognostic impact might be evident.